Theoretical analysis of the 12 min Cooper's test to estimate the maximal oxygen uptake rate. (August 2021) - Alvarez-Ramirez, J.; Rodriguez, E.
Abstract: The Cooper's test is an indirect approach to estimate the maximal oxygen uptake rate ( V ̇ O 2, m a x ) from the maximum distance covered in 12 min exhaustive physical activity. Despite its widespread usage, the 12 min Cooper's test has been scarcely analyzed to assess its validity and potential extensions. The aim of the present work is to obtain a mathematical derivation of the Cooper's equation from a model based on energy conservation and on Newton's second law where resistive and propulsion forces are considered. The main result showed that the Cooper's equation is a particular case of a more general equation, which was validated with field data already published in the literature. Overall, it is concluded that the Cooper's equation is valid over a limited range of distances covered by the 12 min Cooper's test.